Development of Elementary Mathematics Education Teaching Materials based Living Values Education - Nurlaily, Vivi Astuti; Mariyani, Anna (PrimaryEdu : Journal of Primary Education, 2023)
Elementary Mathematics Education is a compulsory subject that must be taken by students of the PGSD Study Program. In fact, there are no practical teaching materials available as facilities for learning activities during lectures as needed. The development of teaching materials for elementary mathematics education courses based on living values education (LVE) is deemed necessary because of the decline in individual character. There are various activities in bringing value education to life, ranging from practice, productivity, and meaning. LVE as a solution and answer to the need for values of human life. The purpose of the study was to produce teaching materials for elementary mathematics education based on living values education. The type of research is research and development (R&D) proposed by Borg and Gall. Based on the steps in the research development cycle that were delivered, they were then shortened to four main stages, are 1) exploration stage or preliminary stage, 2) model development stage, 3) model testing stage, and 4) model dissemination and implementation stage. The results showed that the teaching materials developed had met the valid criteria with a percentage of 86.39% in the material aspect, 82.8% in the language aspect, and 88.7% in the presentation aspect with very good criteria. In addition, the teaching materials developed can improve students' abilities with an average pretest achievement of 76 while the average posttest score of 88. On average, the N-Gain value of 0.5 is obtained, which means that the student's ability is included in the medium category.